Evaluation of exercise based intervention programs for metabolic syndrome - Torres, Georgia (My University, 2014)
Background The optimal exercise load/intensity for exercise programs for individuals with metabolic syndrome (MetS) has not been investigated. One method of determining optimal exercise load is to measure the blood lactate transition threshold (BLTT), referred to as the anaerobic threshold (AT). The first part of this thesis (study 1) investigated the reproducibility of BLTT testing and the consequent determination of AT via the Mader method (Mader et al. 1986) and a modified form of the ADAPT method (Cheng et al. 1992) in patients with MetS. Furthermore, a comparison of the reproducibility of the AT determination using the Mader et al. (1986) method as opposed to the ADAPT method has not been investigated in MetS patients. The effect of specific exercise protocols on the different components of MetS has also not been investigated. Therefore, the second study in the thesis compared the effects on the components of the MetS of an exercise program that uses BLTT (specifically, the AT) to those of a comparable exercise program (not using AT) taken from the literature. The main aim of the study was to design an exercise program that optimized exercise responses and may thus improve metabolic characteristics in individuals with MetS. The third part of the thesis (study 3) focused on the relationship between cardiorespiratory fitness and the components of the metabolic syndrome. This study developed multiple regression models to find the principal variables that associated with peak vi oxygen consumption (VO2 peak) and AT in persons with MetS. Regression models were also developed to investigate whether these variables were associated with the individual metabolic and cardiovascular components of the metabolic syndrome. Methods In study 1, fifteen male patients diagnosed with MetS (age: 43.5 ± 7.52 years) and fifteen healthy, male participants (age: 44.1 ± 6.08 years) each performed a peak oxygen consumption and BLTT test simultaneously using an incremental protocol to exhaustion on a treadmill, at the same daily times, on three different days. Study 2 used three subject groups. One group consisted of ten participants (male, age: 48.3 ± 7.32 years) with MetS that exercised using the walking program of Leon et al. (1979) (MetSL). A second group consisted of ten participants (male, age: 40.8 ± 8.21 years) with MetS that exercised using velocity at AT to set training intensities (MetSV). A third group consisted of ten participants (male, age: 40.2 ± 7.90 years) without MetS that exercised using velocity at AT to set training intensities (Non-MetSV). Training durations and frequency varied from 20 – 90 minutes and 3 -5 days per week respectively. Height, body mass, waist circumference, blood pressure, fasting plasma triglyceride, total cholesterol, HDL-, LDL- cholesterol, insulin levels, VO2 peak and BLTT were measured in all groups before, during and after twenty weeks of exercise. In addition, oral glucose tolerance tests (OGTT) were administered to all participants. 0 min, 30 min and 2 hours plasma glucose and insulin levels were measured during the OGTT. HOMA-IR and insulinogenic indices were also calculated. Nutritional data were recorded at week 0, 8 and 20 of training. vii In study 3, thirty-one males diagnosed with MetS and twenty-four healthy male participants each performed a VO2 peak and a BLTT test. Height, mass, waist circumference, blood pressure, fasting plasma triglyceride, total cholesterol, HDLcholesterol and insulin levels were also measured. In addition, oral glucose tolerance tests (OGTT) were administered to all participants and HOMA indices were calculated. Results There was no significant difference in treadmill velocity at AT determined by the Mader method or the Modified ADAPT method within both groups of study 1 (p > 0.05). The mean treadmill velocity at AT was higher in the healthy compared to the MetS group using both the Mader and the ADAPT method. Regression analysis and ANCOVA in study 1 demonstrated that this difference was largely due to a higher VO2 peak in the healthy group. The study also found an association between VO2 peak and waist circumference. The coefficient of variation of repeat measurements for both the Mader method and the Adapt method was less than 4% indicating good reproducibility. This was confirmed by the typical error method of Hopkins (2000). Study 2 showed that body mass, BMI and waist circumference decreased significantly in all training groups with the training program using AT and the program not using AT showing similar outcomes in these variables among persons with MetS. Velocity at AT also improved in all training groups. While VO2 peak increased (p < 0.05) in both the MetS groups, it did not change significantly in the group without MetS. Similarly, the blood pressure response was favourable in the groups with MetS yet absent in the group viii without MetS. The training group with MetS that used AT was the only group to show significant, positive changes in any of the metabolic parameters (fasting insulin and HOMA). This group also showed the greatest change in the incidence of MetS. In study 3, presence of MetS, waist circumference and AT were found to associate with VO2 peak and VO2 peak was strongly correlated with AT. Age and body mass were found to correlate with fasting glucose, whilst only age correlated with HDL-cholesterol. Age and VO2 peak both correlated with systolic blood pressure but only VO2 peak had a significant association with diastolic blood pressure. Conclusions Study 1 demonstrated that BLTT tests are reproducible in persons with MetS. Study 2 demonstrated that an endurance exercise program using AT to set intensity is effective in eliciting favourable responses in individuals diagnosed with MetS. In addition, the training program using AT elicited the responses with a reduced exercise frequency and intensity. It also improved insulin sensitivity which was not affected by the walking program. The response to the exercise program that used AT was similar in persons with MetS and in persons without MetS, except in the central cardio-vascular adaptations of VO2 peak and in the metabolic parameters of fasting insulin and the HOMA index. Study 3 found that the lower VO2 peak of participants with MetS is associated with their higher waist circumference. The VO2 peak, in turn, was shown to correlate with anaerobic threshold. Therefore, reducing waist circumference in persons with MetS needs to be a focus of intervention programs for such a group. This study also found that both diastolic and systolic blood pressures were associated with cardio-respiratory fitness (VO2 peak). ix This further supports the benefit of increasing cardio-respiratory fitness in persons with MetS. The results of these studies showed that BLTT tests are simple, low-cost, reproducible ways of setting exercise intensity for persons with MetS that can be incorporated in the routine cardio-respiratory fitness assessment of an individual. Furthermore, the determination of AT from such tests can be used to design an individualized exercise program that can “reverse” the effects of MetS.
Keywords: Exercise Therapy; Metabolic Syndrome X